Blue Light and Visual Health: Mechanisms, Risks, and Protective Strategies - Więsyk, Piotr Jan; Urbańska, Karolina; Wójcik, Piotr; Jasiński, Kacper; Wojdat, Aldona (Quality in Sport, 2024)
Introduction: Exposure to blue light throughout the day plays a key role in maintaining the balance of our biological functions. It has a profound impact on our physical and mental state, including the visual system, and contributes to the regulation of behavior and circadian rhythms. The relationship between light emitted by digital devices, the biological rhythm of the retina and the development of refractive errors has been the subject of research in recent years. Aim of Study: This manuscript aims to investigate the implications of light exposure from digital devices on the visual system and circadian rhytms, with a focus on understanding the associated risks, such as digital eye strain and myopia progression. Additionally, the study evaluates the efficacy of blue light-filtering lenses in mitigating these effects. Material and Methods: The present study is based on literature available in scientific databases such as PubMed, Corchane Library and Google Scholar, using the following keywords ,,Digital devices”; ,, Blue light” ; Digital eye strain” ; Visual system”; ,,Circadian rhythms” Results and conclusions: Despite the prevalent use of blue light-filtering lenses, existing evidence indicates that their effectiveness in improving visual performance or preventing retinal damage is limited. Consequently, the implementation of protective strategies, such as the 20-20-20 rule, combined with appropriate ergonomic practices, is critical in alleviating the ocular strain induced by extended screen exposure.